Short Communication: In vitro antimicrobial and antimalarial screening of a crude extract of Streptomyces sp. AB8 isolated from Lapindo Mud Volcano Area, Sidoarjo, Indonesia - Achmad Arifiyanto; Endah Setyaningrum; Nismah Nukmal; Titik Nur Aeny (Society for Indonesian Biodiversity, 2021)
Abstract. Arifiyanto A, Setyaningrum E, Nukmal N, Aeny TN. 2021. Short Communication: In vitro antimicrobial and antimalarial screening of a crude extract of Streptomyces sp. AB8 isolated from Lapindo Mud Volcano Area, Sidoarjo, Indonesia. Biodiversitas 22: 2817-2823. Streptomyces is a potential bacterial genus that has been investigated extensively as a source of natural microbial compounds. Its potential metabolites have been widely developed for pharmaceutical, pathogen control, and other applications in agriculture. This study aimed to determine the ability of the Streptomyces sp AB8 crude extract in inhibiting Plasmodium and pathogenic microbes. Streptomyces was cultured on Gause synthetic media for 10 days. The fermented broth culture media has dissolved in a 1:1 mixture of ethyl acetate and methanol. Biochemical characterization of this isolate has carried out using the standard methods. In-vitro antimalarial activity assay was performed using a chloroquine-sensitive Plasmodium falciparum strain 3D7. Fresh type O-positive human erythrocytes were suspended at 4 percent hematocrit in a complete medium to maintain culture. The inhibitory concentration (IC50) was determined using probit analysis. The results showed the extract of Streptomyces sp. AB8 contains phenolic and alkaloids. Streptomyces sp. AB8 extract can inhibit Dickeya zeae N-Unila 5, Dickeya zeae N-Unila 10, Aspergillus sp IK3, and Escherichia coli growth. The results also showed that the ICs0 value of extract against P. falciparum 3D7 was 17.56 ug/mL. Further research was needed to determine the types of purified bioactive compounds and their bioactivity.